решение на фотографии
Пусть Тогда
Имеем дифференциальное уравнение, однородное относительно переменных.
Подстановка: где
Имеем:
Обратная подстановка:
ответ:
решение на фотографии
Пусть
Тогда ![f(\lambda x;~\lambda y) = \dfrac{(\lambda y)^{2}}{\lambda x\lambda y - (\lambda x)^{2}} = \dfrac{\lambda^{2}y^{2}}{\lambda^{2}xy - \lambda^{2}x^{2}} =](/tpl/images/1477/7747/de026.png)
Имеем дифференциальное уравнение, однородное относительно переменных.
Подстановка:
где ![u = u(x)](/tpl/images/1477/7747/e1640.png)
Имеем:
Обратная подстановка:
ответ:![C = \ln \left|y\right| - \dfrac{y}{x}](/tpl/images/1477/7747/23eec.png)